Caracterização in vivo e in vitro da resposta inflamatória aguda induzida por uma fração proteica isolada do látex de Calotropis procera (Ait.) R. Br - Rabelo, Alana Fonteles Lima (2014)
Calotropis procera is a laticiferous plant belonging to the family Apocynaceae, found in Asia, Africa and South America. Its latex is comprised of a large number of bioactive molecules that show significant pharmacological properties including anti- and pro- inflammatory, antitumor, healing, antimicrobial, among others. The proteins extracted from this latex have multiple immunomodulatory effects, depending on the route of administration utilized. The objective of this study was to characterize the pro- inflammatory response of protein fraction PL latex Calotropis procera in models of peritonitis and subcutaneous air pouch; neutrophil chemotaxis (in vivo and in vitro); the role of resident cells and mediators involved. Swiss mice were used (25-30 g). It was found that PL induced neutrophil migration (MN) in a dose- and time - dependent in models of peritonitis and subcutaneous air pouch. An increase in vascular permeability induced by the administration of PL (1 mg / cav) in the peritoneal cavity in the Evans blue model was demonstrated. The increase in the population of resident macrophages after pre-treatment with thioglycolate intensified the MN induced by PL, with the similar result observed with the mast cell -depleted group by compound 48/80. Mast cells appear to exert an inhibitory modulatory role on neutrophil chemotaxis, whereas macrophages potentiate the MN, possibly through the release of mediators. For investigation of involved mediators, blocking drugs were used before administration of the PL. Pharmacological modulation Dexamethasone (0.5 mg/kg , s.c.), Pentoxifylline (100 mg/kg , s.c.), Thalidomide (50 mg/kg , s.c.), Indomethacin (3 mg/kg , s.c.) and Celecoxib (30 mg/kg , s.c.), but not with Meclizine (40 mg/kg , s.c.) and PCA (10 mg/kg, s.c.) inhibited the MN induced by PL. It was verified by ELISA, that levels of mediators IL-1 and IL-6 were elevated in the peritoneal fluid 4 hours after administration of PL (1 mg/cav, i.p.). The nitrite levels were also higher in the subcutaneous air pouch fluid, demonstrating the involvement of nitric oxide (NO) in the pro-inflammatory effects of LP. PL induced rolling and adhesion of leukocytes to the vascular endothelium of mesenteric mice and neutrophil chemotaxis in vitro. Furthermore, it can directly interact with neutrophils by inducing the synthesis of pro-inflammatory mediators TNF-α, IL- 1β, PGE2 and NO in neutrophil’s culture. In conclusion, PL induces an acute inflammatory response characterized by intense neutrophil migration and increase of vascular permeability. Promotes neutrophil chemotaxis indirectly, via resident macrophages and directly interacting with neutrophils, inducing rolling and adhesion to the endothelium and release of pro-inflammatory mediators.